The Role of the Risk Management Committee in Managing Supply Chain Risk and Enhancing Supply Chain Performance: An Emerging Market Perspective - Andhyka Tyaz Nugraha; Hadiati Fitri; Marlina Widiyanti; Rahmad Guntoro; Sulastri . (International Journal of Supply Chain Management, 2019)
The prime objective of the currents study is to examine the role of the risk management committee in managing the supply chain risk and enhancing the supply chain performance. The three risk measures namely supply chain technology risk, supply chain integration risk and supply chain integration risk are used to conceptualize the firm supply chain risk. The risk management committee is one of a feature of the code of corporate governance which during the last couple of years have widely discussed in the literature in the reference of financial risk management. However, little or no attention has been given to explore the issue with the reference of operational risk management, especially in supply chain risk management. This is among the few pioneering studies being carried out to explore the direct role of risk management committee on firm supply performance and its moderating role on firm supply chain risk and firm supply performance. The SEM-PLS is used to achieve the research objectives. The data is collected from the operation managers of Indonesian based production firms operating in Indonesia. The results of the study have shown a great deal of agreement with our proposed hypothesis. Except the supply chain integration risk, all other measures of risk are in a significant positive relation with firm supply performance whereas the supply chain integration risk appears in negative and significant relation with the firm supply chain performance. The current study will be helpful for PR actioners, researchers and policy makers in understanding the link between operational management and corporate governance.